Relations between executive function and academic achievement from ages 5 to 17 in a large, representative national sample - Best, John R.; Miller, Patricia H.; Naglieri, Jack A. (Learning and individual differences, 2011)
This study examined age-related changes in complex executive function (EF) in a large, representative sample ( N = 2036) aged 5 to 17 using the Cognitive Assessment System (CAS; Naglieri & Das, 1997a). Relations between complex EF and academic achievement were examined on a sub-sample (N = 1395) given the Woodcock–Johnson Tests of Achievement–Revised (Woodcock & Johnson, 1989). Performance on the three complex EF tasks improved until at least age 15, although improvement slowed with increasing age and varied some across tasks. Moreover, the different developmental patterns in the correlations between completion time and accuracy provide clues to developmental processes. Examination of individual achievement subtests clarified the specific aspects of academic performance most related to complex EF. Finally, the correlation between complex EF and academic achievement varied across ages, but the developmental pattern of the strength of these correlations was remarkably similar for overall math and reading achievement, suggesting a domain-general relation between complex EF and academic achievement. ►Current study utilized a large, nationally-represented sample of children. ►Complex EF developed significantly until at least age 15. ►Metacognition appears to aid EF development. ►Both domain-general relations and intra-domain variability to achievement were discovered.